2006
DOI: 10.17221/5589-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding treated peat as a supplement to newborn piglets on the growth, health status and occurrence of conditionally pathogenic mycobacteria

Abstract: The first purpose of this experiment was to investigate the effect of ad libitum feeding of peat as a supplement to piglets from the age of five days up 23 days of age on their growth performance and health status. The second purpose was to assess the risk of the occurrence of conditionally pathogenic mycobacteria (CPM) in peat treated with ionizing radiation (Group PI) or per acetic acid (Group PP) and fed as a supplement to piglets. In respective experimental periods (at the age of 4, 23, 41 and 67 days), no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…According to some authors (Ji et al, 2006;Wang et al, 2008), growing pigs fed diets containing HS showed a larger average daily gain, but average daily feed intake was unaffected. However, Trckova et al (2006) found no difference in the growth performance of pigs fed diets supplemented with HS. Further research is necessary to determine the cause of the disparity in growth performance.…”
Section: Discussionmentioning
confidence: 80%
“…According to some authors (Ji et al, 2006;Wang et al, 2008), growing pigs fed diets containing HS showed a larger average daily gain, but average daily feed intake was unaffected. However, Trckova et al (2006) found no difference in the growth performance of pigs fed diets supplemented with HS. Further research is necessary to determine the cause of the disparity in growth performance.…”
Section: Discussionmentioning
confidence: 80%
“…The highest concentration of mycobacteria (65 to 74%) was found in commercially available peat packed in unsealed plastic bags, intended for gardening or as a feed supplement for pigs. The most commonly isolated species was M. a. hominissuis Trckova et al, 2006). Certain companies started to treat peat-based feed supplements with ionising irradiation with the aim to decrease contamination of peat with conditionally pathogenic mycobacteria (non-published data).…”
mentioning
confidence: 99%